On Vector Valued Paranormed Sequence Space l (X,M, ?, p,L) Defined by Orlicz Function - Pahari, Narayan Prasad (Nepal Journal of Science and Technology, 2012)
DOI: http://dx.doi.org/10.3126/njst.v12i0.6510 Nepal Journal of Science and Technology 12 (2011) 252-259